Nonlinear dynamic response analysis of buildings for wind loads. A new frontier in the structural wind engineering. (15th April 2022) - Iancovici, Mihail; Ionică, Georgiana; Pavel, Florin; Moța, Florin; Nica, George Bogdan
Abstract: The structural engineering practitioners often deal with natural hazards that generate a structural response that is dynamic in nature. The wind loads are long duration load types and their induced effects, especially for severe events, need to be predicted through analysis by efficient numerical nonlinear solvers. In this paper the nonlinear wind-induced effects on structures are predicted using a non-commercial software based on the 3D Force Analogy Method (3D-FAM). The wind loads consist of time-histories of pressure coefficients recorded at a large number of taps in the wind tunnel test for a model corresponding to an 80 m high prototype building. A considerable number of dynamic nonlinear analyses are performed for different mean hourly wind speeds and wind blowing directions. For each case, the inelastic behavior of building is monitored through and efficient complementary energy balance-based analysis and quantified in time-domain by damage indices at each section, element, story and structural level. Highlights: In the light of ASCE 2019 Pre-standard, the FAM3D approach opens a door for performance-based design for wind loads. The decoupling of the capacity function ensured a good balance between accuracy and speed. Nonlinear dynamic analysis to wind loads will produce insights in the damage evaluation.